Increasing the Science Learning Outcomes Through the Outdoor Learning Method in Children with Special Needs grade IV at the Inclusive Primary School - Mitta Purbosari, Para; Angganing, Paradika; Sutrisno, Tri; Ahmadi, Farid; Permata Hapsari, Intan (International Journal of Psychosocial Rehabilitation, 2019)
The aim of this research is to improve the learning outcomes of Natural Sciences in Grade IV Semin IV Primary School GunungKidul District through outdoor learning for students with special needs. This research is class action research. Actions carried out two cycles. Data analysis techniques use techniques Qualitative and quantitative. In the first cycle using Outdoor Learning by visiting a direct object, the number of students complete with a percentage of learning is 55.56%. The Outdoor Learning in second cycle by involving elements of play is 88.89%. The conclusion of this research is that the use and application of Outdoor Learning can improve science learning outcomes of students grade IV Semin IV Primary School GunungKidulDistrict